2018
DOI: 10.1080/2162402x.2018.1518672
|View full text |Cite
|
Sign up to set email alerts
|

Virotherapy-recruited PMN-MDSC infiltration of mesothelioma blocks antitumor CTL by IL-10-mediated dendritic cell suppression

Abstract: Antitumor cytotoxic T lymphocytes (CTLs) are essential for immune surveillance, yet the blockade of eliciting such CTLs during oncolytic virotherapy remains incompletely understood. Here, we show that oncolysis of mesothelioma by modified vaccinia Tiantan (MVTT) induces damage-associated molecular patterns exposure. Although MVTT leads to regression of established mesothelioma dose-dependently, antitumor CTLs are rarely induced. Mechanistically, MVTT virotherapy generates C-X-C chemokines that recruit CXCR2-ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 69 publications
(107 reference statements)
2
24
0
Order By: Relevance
“…[ 146 ] have reported that endostatin can achieve such goals in lung cancer by limiting the recruitment of MDSCs and decreasing the production of anti-inflammatory cytokines, including IL-10 among others. Consistent with this view, Tan et al [ 147 ] have shown that depletion of MDSCs, particularly IL-10-producing PMN-MDSCs, which can inhibit DCs that activate anti-tumour cytotoxic T cell responses, can enhance the therapeutic efficacy of modified vaccinia Tiantan strain by inducing anti-tumour cytotoxic T cell responses in mesothelioma. Treatment with zoledronic acid impaired the accumulation of MDSCs to the tumour site resulting in delayed tumour growth rate, and increased recruitment of T cells to the tumour and prolonged the overall survival [ 148 ].…”
Section: Mdsc/il-10 As a Therapeutic Targetmentioning
confidence: 84%
“…[ 146 ] have reported that endostatin can achieve such goals in lung cancer by limiting the recruitment of MDSCs and decreasing the production of anti-inflammatory cytokines, including IL-10 among others. Consistent with this view, Tan et al [ 147 ] have shown that depletion of MDSCs, particularly IL-10-producing PMN-MDSCs, which can inhibit DCs that activate anti-tumour cytotoxic T cell responses, can enhance the therapeutic efficacy of modified vaccinia Tiantan strain by inducing anti-tumour cytotoxic T cell responses in mesothelioma. Treatment with zoledronic acid impaired the accumulation of MDSCs to the tumour site resulting in delayed tumour growth rate, and increased recruitment of T cells to the tumour and prolonged the overall survival [ 148 ].…”
Section: Mdsc/il-10 As a Therapeutic Targetmentioning
confidence: 84%
“…Some studies have shown that METTL3 expression can promote tumour cell proliferation, leading to poor patient prognosis. The tumour-infiltrated MDSC population usually induces antitumour immunity tolerance by inhibiting the proliferation and function of T cells, such as hindering antigen presentation by antigen-presenting cells [ 36 ]. Increased METTL3 levels and CD33 + MDSCs have been found in tumour microenvironments and lead to a poor prognosis [ 37 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that METTL3 expression can promote tumour cell proliferation, leading to poor patient prognosis. The tumour-in ltrated MDSC population usually induces antitumour immunity tolerance by inhibiting the proliferation and function of T cells, such as hindering antigen presentation by antigen-presenting cells (36). Increased METTL3 levels and CD33 + MDSCs have been found in tumour microenvironments and lead to a poor prognosis (37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%